The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3390/socsci7060092
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Healthcare Opportunities for Improved Access among Ghanaian Retirees: The Case of Active Aging

Abstract: This paper is a policy brief with targeted interviews of older adults in urban Ghana with recommendations for future healthcare policy. Using qualitative explorative approach, the scope of the research is to examine opportunities that focus on healthy aging in order to enhance healthcare infrastructure in Ghana in preparation for an increased number of older adults. The paper mainly finds that improved healthcare solicitation and the social world of older adults are intricately linked. The healthcare needs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Zaidi (2015) posits that preretirement planning facilitates increased financial security, improve health and well-being including age-friendly infrastructure. Financial security may be reflective of a regular retirement income (Adzawla et al, 2015;Dovie, 2018), whether sufficient or otherwise. Research (e.g., Snyman et al, 2017) has shown that finances are the strongest single predictor of the decision to retire and that people are more likely to leave the workforce if they can financially afford to retire than if they cannot.…”
Section: Resultsmentioning
confidence: 99%
“…Zaidi (2015) posits that preretirement planning facilitates increased financial security, improve health and well-being including age-friendly infrastructure. Financial security may be reflective of a regular retirement income (Adzawla et al, 2015;Dovie, 2018), whether sufficient or otherwise. Research (e.g., Snyman et al, 2017) has shown that finances are the strongest single predictor of the decision to retire and that people are more likely to leave the workforce if they can financially afford to retire than if they cannot.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, van der Geest [29] found that "The NHIS prescribes the same basic healthcare without taking into consideration the tertiary healthcare needs of older people especially in the area of NCDs including retention of urine, incontinence, prostrate and colon cancers" (p. 11). Pensioners' association membership nationwide has benefits which encompass participation in the pensioners' medical scheme, a complement to NHIS, among others [21].…”
Section: Discussionmentioning
confidence: 99%
“…Such money could be channeled into meeting select survival needs [5]. This is a factor in the relatively low levels of pension incomes in Ghana [21].…”
Section: Housing Issues In Ghanamentioning
confidence: 99%
See 1 more Smart Citation
“…Such money could be channeled into meeting select survival needs. The essence of this lies in the relatively low levels of pension incomes in Ghana (Dovie, 2018a).…”
Section: Importance Of Owning a House In Post-retirement Lifementioning
confidence: 99%